Boekbespreking (OverHolland, 2005)
Wim Denslagen Romantisch modernisme: Nostalgie in de monumentenzorgAmsterdam (SUN) 2004, 255 pp.Andrés Duany, Elizabeth Plater-Zyberk, Robert Alminana (red.)The new civic art: Elements of Town PlanningNew York (Rizzoli) 2003, 416 pp.